Does bank efficiency influence the cost of credit? - Shamshur, Anastasiya; Weill, Laurent (Journal of Banking & Finance, 2019)
Using a large sample of firms from nine European countries, this study examines the relationship between bank efficiency and the cost of credit for borrowing firms. We hypothesize that bank efficiency – the ability of banks to operate at lower costs – is associated with lower loan rates and thus lower cost of credit. Combining firm-level and bank-level data, we find support for this prediction. The effect of bank efficiency on the cost of credit varies with firm and bank size. Bank efficiency reduces the cost of credit for SMEs, but does not exert a significant influence for either micro companies or large firms. Furthermore, the effect is driven by large banks, where improvements in bank efficiency tend to be strongly associated with lower cost of credit. We also find that lower bank competition facilitates the transmission of greater bank efficiency to lower cost of credit. Overall, our results indicate that measures that increase bank efficiency can foster access to credit.